Simultaneous quantification of abemaciclib and letrozole in rat plasma: method development, validation and pharmacokinetic application. (31st March 2020) - Dhakne, Pooja; Sahu, Amit Kumar; Sharma, Manish Kumar; Sengupta, Pinaki
Abstract: Treatment through a combination of drugs involving cyclin D‐dependent kinase inhibitors like abemaciclib and aromatase inhibitor like letrozole proved to be a potential therapeutic regimen and first‐line treatment in estrogen receptor‐positive breast cancer. In this study, we developed a simple and simultaneous RP‐HPLC bioanalytical method for quantifying abemaciclib and letrozole in rat plasma. Abemaciclib and letrozole were separated on Zorbax Eclipse C18 column employing a gradient elution method comprising 10 mM ammonium acetate (pH 5) and acetonitrile as mobile phase. The method was found to have acceptable selectivity, accuracy (97.20–118.17%), precision (1.10–9.39%) and stability in the validation experiment performed as per the US Food and Drug Administration guidelines. The method sensitivity was low at a concentration level of 100 ng/ml. The applicability of the method has been verified through a single‐dose oral pharmacokinetic study in rat. The developed method will be useful to quantitate the analytes in rat plasma samples of different preclinical studies including their pharmacokinetic drug–drug interactions in the future. To date, no method has been reported for the quantification of abemaciclib and letrozole simultaneously in any type of biological matrices. Therefore, this study makes a definite significant contribution in the field of bioanalytical research.